Społeczno-gospodarcze uwarunkowania skuteczności bojowej Kozackiego Wojska Zabajkalskiego w wojnie rosyjsko-japońskiej 1904–1905 - Igielski, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
This text is about role of Transbaikal Cossack community during Russ-Japan War of 1904–1905, with particular emphasis on influence of their social and economic situation on military effectiveness. Transbaikal Cossacks were the biggest part of Cossack forces and cavalry on the theater of operations in Manchuria. They had excellent horses but also lack of military experience and bad training of soldiers, which led to lack of, expected before the war, important successes on the battlefield, in cavalry raids and during distant reconnaissance. They had mostly not enough brave and trained soldiers to spectacular charges on horseback and to fight with enemy’s cavalry on armee blanche. Conclusions are as follow: Transbaikal Cossack community in the realities of the early 20 th century modern warfare was emanation of anachronic formation from earlier ages.
Socio-economic determinants of combat effectiveness of the Transbaikal Cossack Host during the Russo-Japanese War 1904–1905
Keywords: Russo-Japanese War; Russian Cavalry; Cossacks in czarist army; Transbaikal Cossack Host